A biophysical model of viral escape from polyclonal antibodies. Issue 2 (12th December 2022) - Yu, Timothy C; Thornton, Zorian T; Hannon, William W; DeWitt, William S; Radford, Caelan E; Matsen, Frederick A; Bloom, Jesse D
Abstract: A challenge in studying viral immune escape is determining how mutations combine to escape polyclonal antibodies, which can potentially target multiple distinct viral epitopes. Here we introduce a biophysical model of this process that partitions the total polyclonal antibody activity by epitope and then quantifies how each viral mutation affects the antibody activity against each epitope. We develop software that can use deep mutational scanning data to infer these properties for polyclonal antibody mixtures. We validate this software using a computationally simulated deep mutational scanning experiment and demonstrate that it enables the prediction of escape by arbitrary combinations of mutations. The software described in this paper is available at https://jbloomlab.github.io/polyclonal .